SDHB mutations are associated with response to temozolomide in patients with metastatic pheochromocytoma or paraganglioma. Issue 11 (5th May 2014) - Hadoux, Julien; Favier, Judith; Scoazec, Jean‐Yves; Leboulleux, Sophie; Al Ghuzlan, Abir; Caramella, Caroline; Déandreis, Désirée; Borget, Isabelle; Loriot, Céline; Chougnet, Cécile; Letouzé, Eric; Young, Jacques; et al.
<x xml:space="preserve">Abstract</x> Cyclophosphamide–dacarbazine–vincristine regimen is recommended for the treatment of malignant pheochromocytoma and paraganglioma (MPP); however, dacarbazine is the only recognized active drug in neuroendocrine tumours. We investigated the therapeutic benefit of temozolomide (TMZ), an oral alternative to dacarbazine, in patients with MPP. This is a retrospective study of consecutive patients with documented progressive MPP. We examined the correlation between Succinate dehydrogenase B (SDHB) mutation and O(6)‐methylguanine‐DNA methyltransferase (MGMT) promoter methylation and MGMT expression in the French nation‐wide independent cohort of 190 pheochromocytomas or paragangliomas (PP). Progression‐free survival (PFS) according to RECIST 1.1 and PERCIST 1.0 criteria was the primary end point. Fifteen consecutive patients with MPP were enrolled; ten (67%) carried a mutation in SDHB. The mean dose intensity of TMZ was 172 mg/m2/d for 5 days every 28 days. Median PFS was 13.3 months after a median follow‐up of 35 months. There were five partial responses (33%), seven stable (47%) and three progressive diseases (20%). Grade 3 toxicities were lymphopenia in two patients and hypertension in one. Partial responses were observed only in patients with mutation in SDHB. MGMT immunohistochemistry was negative in tumour samples from four patients who responded to treatment. SDHB germline mutation was associated with hypermethylation of the MGMT promoter and low expression of MGMT in 190 samples of the French nation‐wide independent cohort. This study demonstrates that TMZ is an effective antitumour agent in patients with SDHB‐related MPP. The silencing of MGMT expression as a consequence of MGMT promoter hypermethylation in SDHB‐mutated tumours may explain this finding.